Development of a Questionnaire and its Content Validitation to Assess Ashta Ahara Vidhi Visheshayatana with Special Reference to Upayoga Samstha in Patients Suffering from Type-2 Diabetes Mellitus - Dr. Saurabh Agrawal,; Dr. Aparna Bagul,; Dr. Asha K.P, (The Bioscan, 2025)
Aims and Objectives: The study aims to develop a comprehensive questionnaire to assess the Ashta Ahara Vidhi Visheshayatana (eight specific dietary considerations) with special reference to Upayoga Samstha (rules for consumption) in patients suffering from Type-2 Diabetes Mellitus (T2DM) and to establish its content validity. Methods: A mixed-method approach was employed, involving qualitative and quantitative phases. Initially, an extensive literature review was conducted to identify relevant constructs and develop a preliminary questionnaire. This was followed by expert validation through the Delphi method to refine the items. Content validity was assessed using the Content Validity Index (CVI). Results: The preliminary questionnaire consisted of 50 items. Through iterative rounds of expert review, the questionnaire was refined to 44 items. The overall CVI was found to be 0.90, indicating high content validity. Conclusion: The developed questionnaire demonstrates good content validity and can be used to assess adherence to Ashta Ahara Vidhi Visheshayatana in patients with T2DM. Future studies should focus on its reliability and construct validity in larger populations.